2011
DOI: 10.1002/acp.1816
|View full text |Cite
|
Sign up to set email alerts
|

Task‐Related Factors that Influence the Spontaneous Use of Diagrams in Math Word Problems

Abstract: Diagrams are effective tools for problem solving. However, previous findings indicate that students generally do not use diagrams spontaneously. This study examined task-related factors that may influence the spontaneity of diagram use. Experiment 1 compared two possible explanations: the first, that the length-relatedness of the story context of the problem (i.e. whether it involves the measurement of length) determines the likelihood of diagram use; and the second, that the cognitive cost of transforming the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 30 publications
(42 reference statements)
0
33
0
1
Order By: Relevance
“…Students also need to overcome hurdles associated with thinking that drawing diagrams is too diffi cult or too costly in terms of mental effort (1,8,9). There are some projects aimed at addressing these problems (10,11).…”
Section: Drawing Attention To Diagram Usementioning
confidence: 99%
“…Students also need to overcome hurdles associated with thinking that drawing diagrams is too diffi cult or too costly in terms of mental effort (1,8,9). There are some projects aimed at addressing these problems (10,11).…”
Section: Drawing Attention To Diagram Usementioning
confidence: 99%
“…Students also need to overcome hurdles associated with thinking that drawing diagrams is too diffi cult or too costly in terms of mental effort (1,8,9). There are some projects aimed at addressing these problems (10,11).…”
Section: Editorial Expression Of Concernmentioning
confidence: 99%
“…One explanation that has been proposed to account for such inadequacies in performance is that some forms of diagrams may entail greater cognitive cost to process—in other words, that they may demand more mental resources and effort to use (Cromley, Snyder‐Hogan, & Luciw‐Dubas, ; Manalo & Uesaka, , ; Uesaka & Manalo, ). This explanation is in part based on the fact that diagrams “distort the ‘truth’” when they “abstract, schematize, supplement, and distort the world outside onto the world of a page” (Tversky, , p. 502).…”
mentioning
confidence: 99%
“…The researchers also found that students often ignored or only superficially looked over diagrams while they were going through the passages—manifesting what could have been avoidant behavior and suggesting that comprehending those diagrams might have demanded a higher cognitive cost compared to comprehending the running text. Likewise, creating diagrams that represent information in more abstract forms, such as charts, may entail higher cognitive cost compared to simply drawing what is described in the given information (Uesaka & Manalo, ). In the Uesaka and Manalo study, junior high school students were given math word problems to solve and their use of diagrams in attempts at solving those problems were examined.…”
mentioning
confidence: 99%
See 1 more Smart Citation